2022
DOI: 10.1002/adfm.202200801
|View full text |Cite
|
Sign up to set email alerts
|

An Injectable Hydrogel Reshaping Adenosinergic Axis for Cancer Therapy

Abstract: Adenosinergic axis, an innate negative feedback mechanism known as converting adenosine triphosphate (ATP) to adenosine by ectonucleotidases CD39 and CD73, reverses the ATP‐mobilized immunogenic tumor microenvironment (TME) to an immunosuppressive TME caused by adenosine, incapacitating various immune cells (especially effector T cells) in tumor elimination. Herein, for the first time, an injectable hydrogel strategy to reshape the adenosinergic axis by metabolizing adenosine into the immunopotentiator compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Inhibition of adenosine generation and signaling pathways have been shown to effectively block the denosine-A2AR pathway ( 131 ). Recently, Zhao et al ( 132 ) introduced adenosine deaminase (ADA) into hydrogels, which enabled the catalytic transformation of adenosine (immunosuppressor) into inosine (an immunopotentiator), thus reversing tumor immunosuppression and enhancing antitumor immune responses.…”
Section: Strategies For Hydrogel-based Cancer Vaccine To Initiate An ...mentioning
confidence: 99%
“…Inhibition of adenosine generation and signaling pathways have been shown to effectively block the denosine-A2AR pathway ( 131 ). Recently, Zhao et al ( 132 ) introduced adenosine deaminase (ADA) into hydrogels, which enabled the catalytic transformation of adenosine (immunosuppressor) into inosine (an immunopotentiator), thus reversing tumor immunosuppression and enhancing antitumor immune responses.…”
Section: Strategies For Hydrogel-based Cancer Vaccine To Initiate An ...mentioning
confidence: 99%
“…Unlike immunosuppressive adenosine, inosine is an alternative energy source for effector T cells and supplements the energy supply of T cells in a glucose-deficient microenvironment to prevent T cell nutrient depletion ( 44 ). Therefore, synergistic transport of ADA with ICD-inducing drugs reduces the accumulation of adenosine in the TMEs and achieves cascade amplification of ATP-activated antitumor immunity ( 40 ). As Zhao et al reported, the injectable hydrogel composed of sodium alginate, ADA, DOX, and autophagy inducer was constructed ( 40 ).…”
Section: Targeting Adenosine Based On Biomaterials For Cancer Immunot...mentioning
confidence: 99%
“…Therefore, synergistic transport of ADA with ICD-inducing drugs reduces the accumulation of adenosine in the TMEs and achieves cascade amplification of ATP-activated antitumor immunity ( 40 ). As Zhao et al reported, the injectable hydrogel composed of sodium alginate, ADA, DOX, and autophagy inducer was constructed ( 40 ). Sodium alginate was chelated with calcium ions enriched in the TMEs to form an in situ hydrogel.…”
Section: Targeting Adenosine Based On Biomaterials For Cancer Immunot...mentioning
confidence: 99%
“…PC cells undergo a metabolic switch from oxidative phosphorylation to glycolysis, causing them to synthesize adenosine triphosphate (ATP) from glucose via glycolysis without oxygen [ 34 ]. It has been reported that the relationship between energy metabolism and autophagy creates a relationship between autophagic activity and cellular ATP levels [ 35 , 36 ]. However, inhibition of ATP production via carbon source deprivation or ATP synthesis perturbation suppresses autophagic activity [ 37 ].…”
Section: Molecular Pathway Of the Autophagy Processmentioning
confidence: 99%